3D topographical analysis for defect detection during loading of woven thermoplastic composites. (January 2022) - Holmes, John; Das, Raj; Stachurski, Zbigniew; Compston, Paul
Abstract: The behaviour of the local weave architecture during large deformation influences the final composite properties, but this architecture is challenging to measure experimentally. In this work, a technique is proposed to examine the local out-of-plane topography of woven composites to improve defect and damage detection during deformation, using digital image correlation (DIC). Three load cases are presented to demonstrate the technique: tension–torsion in a universal testing machine, varied deformation mode testing, and thermo-forming, the latter two both using a hemispherical forming apparatus. Topographical results are found for all cases and show features that are not visible in the surface strain map, providing additional insight into weave response and defect progression. These topographical features include edge delamination, local fibre waviness under biaxial deformation, and undulating weave architecture under thermo-mechanical loading. Graphical abstract: Highlights: Novel technique for measuring topography during forming and combined loading. Three loading cases tested: tension–torsion, biaxial deformation, thermo-forming. Insights for delamination & architecture defects in woven thermoplastic composites. Potential immediate application to many mechanical testing procedures using DIC.